2021
DOI: 10.1002/slct.202100747
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosion Inhibition Behavior of Rhus Pentaphylla Fruit Extracts in (1 M) HCl against Carbon Steel and their Chemical Characterization using HPLC‐MS‐ESI

Abstract: Phenolic compounds in Tunisian wild Rhus pentaphylla fruits during two maturity stages are identified by LC-MS-ESI. The corrosion inhibition efficiency of their extracts was analyzed by the use of polarization curves and electrochemical impedance spectroscopy. The qualitative analysis highlighted the presence of 11 phenolic compounds in total (3 phenolic acids and 8 flavonols) for the un-ripe stage (S1), 7 compounds (1 phenolic acid and 6 flavonols) have been identified for the fully-ripe stage (S2). The elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The plants are natural, local and their availability are easy, which may make them promising inhibitors for the the industrial applications.Many natural plants or their extracts,i. e. taraxacum officinale extract, [19] rhus pentaphylla fruit extracts, [20] hyalomma tick extract, [21] lavandula mairei extract, [22] hemerocallis fulva, [23] arthrospira platensis extract, [24] centipeda minima leaves extract, [25] liriope platyphylla extract, [26] and gloriosa superba seeds [27] have reported as effective corrosion inhibitors against different metals.Thirupathi et al [28] studied an ethanolic extract of portulaca quadrifida (PQ) leaves and synergistic effect between PQ and Zn 2 + ions on the inhibition of carbon steel in well-water. The authors reported 92 % inhibition efficiency in the presence of PQ and Zn 2 + due to possible synergism between them.…”
Section: Introductionmentioning
confidence: 99%
“…The plants are natural, local and their availability are easy, which may make them promising inhibitors for the the industrial applications.Many natural plants or their extracts,i. e. taraxacum officinale extract, [19] rhus pentaphylla fruit extracts, [20] hyalomma tick extract, [21] lavandula mairei extract, [22] hemerocallis fulva, [23] arthrospira platensis extract, [24] centipeda minima leaves extract, [25] liriope platyphylla extract, [26] and gloriosa superba seeds [27] have reported as effective corrosion inhibitors against different metals.Thirupathi et al [28] studied an ethanolic extract of portulaca quadrifida (PQ) leaves and synergistic effect between PQ and Zn 2 + ions on the inhibition of carbon steel in well-water. The authors reported 92 % inhibition efficiency in the presence of PQ and Zn 2 + due to possible synergism between them.…”
Section: Introductionmentioning
confidence: 99%